Effect of hypercholesterolemia on hypertension-induced renal injury in rats: Insights in the possible mechanisms - Ahmed O Abdel-Zaher; Hanan SM Farghaly; Abeer EM El-Refaiy; Ahmed M Abd-Eldayem (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
The effect of hypercholesterolemia on hypertension-induced renal injury was investigated in rats. Hypertension was induced by L-N(G)-nitroarginine methyl ester (L-NAME) and Hypercholesterolemia was induced by feeding rats with a diet containing 1% cholesterol. In these animals L-NAME produced a progressive increase in the systolic, diastolic and mean arterial Blood Pressure (BP). Similarly, L-NAME with hypercholesterolemia produced, in addition to compromised serum lipid profile, a progressive increase in the systolic, diastolic and mean arterial BP. Hypercholesterolemia enhanced the hypertensive effect of L-NAME. Also, hypercholesterolemia enhanced hypertension-induced renal injury as assessed by measurement of serum renal function markers and by histopathological examination. Concomitantly, hypertension-induced elevation of renal tissue Malondialdehyde (MDA) and nitrite levels and reduction of intracellular reduced Glutathione (GSH) level were enhanced by hypercholesterolemia. In addition, hypertension -induced increases in tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β) and Intercellular Adhesion Molecule-1 (ICAM-1) levels in renal tissues were increased by hypercholesterolemia. These results indicate that hypercholesterolemia has the ability to enhance hypertension-induced renal injury. The ability of hypercholesterolemia to provide this effect may positively correlate to its ability to increase renal oxidative stress, nitrosative stress and inflammation.